Energy management of microgrid based on day-ahead and short-term optimisation. (5th October 2020) - Wang, Xiaohui; Zheng, Yiming
Microgrid is an effective way to accept distributed renewable energy. However, due to the uncontrollable and intermittent nature of renewable energy, coupled with the complex operational modes of microgrid, the scheduling of microgrid is more difficult to optimise and control. So it has become a key issue to optimise the coordinated operation of distributed generation units, energy storage devices and loads in energy management of microgrid. In order to guarantee the stable operation, an optimisation scheduling strategy with multiple time scales is proposed in this paper. Based on an independent microgrid, the output power of the equipment units in the microgrid is modelled and the objective functions and constraint conditions are determined. A day-ahead and short-term optimisation scheme is carried out and the scheduling program and combination of each distributed generator are optimised by the particle swarm optimisation (PSO) algorithm. The simulation results are analysed and summarised to verify the feasibility and validity of the proposed optimisation strategy.